Evaluating the Effects of Testosterone Therapy on Cardiometabolic Health and Well-being in Men with Hypogonadism - Azza Fithra Alhanifa; Nyoman Bayu Rusdyana Krisna (PP PERKENI, 2025)
Testosterone is crucial for male health, and hypogonadism is prevalent, particularly in men with metabolic comorbidities. While Testosterone Therapy (TTh) is used to manage symptoms, itseffects on cardiometabolic health and overall well-being remain debated. This review aimed to synthesize current evidence on the impact of TTh on cardiometabolic parameters, cardiovascularsafety, and quality of life in men with hypogonadism. A literature search (2015-2025) across multiple databases identified relevant studies, including Randomized Controlled Trials (RCTs) andobservational data, which were narratively synthesized. Results show TTh consistently improves body composition (reduced fat, increased muscle) and aspects of sexual function (libido, activity).However, its effect on glucose metabolism remains controversial, with conflicting findings. While large RCTs indicate no increased risk of major adverse cardiovascular events over the medium term,TTh is associated with increased specific risks including pulmonary embolism, atrial fibrillation, acute kidney injury, and polycythemia. Benefits on mood/energy are modest, and effects on otherquality of life domains are limited. In conclusion, TTh offers clear benefits for body composition and sexual function. Clinicians must balance these with controversial glucose effects and increasedspecific adverse event risks, requiring careful patient selection and monitoring. Further long-term research is needed.